2022
DOI: 10.3892/etm.2022.11242
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin A alleviates lipopolysaccharide‑induced inflammation and apoptosis in pulmonary microvascular endothelial cells and permeability injury by inhibiting STAT3 signaling

Abstract: Glaucocalyxin A (GLA), an ent-kauranoid diterpene derived from Rabdosia japonica var. glaucocalyx, possesses antibacterial, anti-oxidative and anti-neuroinflammatory properties. The present study aimed to investigate the potential mechanisms underlying GLA in the pathogenesis of pneumonia. Human pulmonary microvascular endothelial cells (hPMVECs) treated with lipopolysaccharide (LPS) were treated with GLA, followed by the detection of cell viability, inflammation, apoptosis and cell permeability. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Pneumonia is a form of acute respiratory infection that affects the lungs 19 . Many studies have reported the critical role of inflammation in the progression of pneumonia 20 . Nuclear factor‐kappa B is a dimeric transcription factor involved in host immune response, inflammation, cell proliferation, cell adhesion, growth signals, apoptosis defense, and cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumonia is a form of acute respiratory infection that affects the lungs 19 . Many studies have reported the critical role of inflammation in the progression of pneumonia 20 . Nuclear factor‐kappa B is a dimeric transcription factor involved in host immune response, inflammation, cell proliferation, cell adhesion, growth signals, apoptosis defense, and cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Many studies have reported the critical role of inflammation in the progression of pneumonia. 20 Nuclear factor‐kappa B is a dimeric transcription factor involved in host immune response, inflammation, cell proliferation, cell adhesion, growth signals, apoptosis defense, and cell differentiation. NF‐κB act as a principal component for pneumonia, asthma, COPD, and other inflammatory lung diseases.…”
Section: Discussionmentioning
confidence: 99%